2018
DOI: 10.17235/reed.2018.5468/2018
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of the use of proton pump inhibitors in the Emergency Department of a Spanish university hospital

Abstract: Background: the use of proton pump inhibitors (PPI) has increased substantially during the last years, possibly due to a significant proportion of prescriptions that do not follow the approved indications. Objective: to assess the prevalence of PPI prescription and the appropriateness of the prescription within the Emergency Department (ED) of a Spanish university hospital. Materials and methods: a cross-sectional, retrospective prescription-indication drug-use study was performed, which selected 384 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…First, it is important to regularly reassess the need for ongoing treatment with PPI and how the risks can be reduced when prescribing PPI. Second, PPI over-use should be controlled by limiting the appropriateness of reimbursement, over-prescription and improving the distribution of therapeutic recommendation guidelines (27). Third, more studies should define the appropriate indications of PPI use, investigate the exact causality between risk and PPI use and also develop alternate management options for acid peptic diseases (24,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it is important to regularly reassess the need for ongoing treatment with PPI and how the risks can be reduced when prescribing PPI. Second, PPI over-use should be controlled by limiting the appropriateness of reimbursement, over-prescription and improving the distribution of therapeutic recommendation guidelines (27). Third, more studies should define the appropriate indications of PPI use, investigate the exact causality between risk and PPI use and also develop alternate management options for acid peptic diseases (24,28).…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate PPI use and the associated risks have dramatically increased over the last few decades (2,(4)(5)(6). Emerging post-marketing studies have demonstrated that inappropriate PPI use has become a major clinical problem (2,7,8). Several case-control, cohort and meta-analyses studies have reported that PPI use increased the risk of various adverse effects including kidney disease (9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%